DESAIN SISTEM KADAR AIR DALAM TANAH DENGAN BERBASIS ARDUINO UNO - Gilang Adel Kuswara; Muhammad Miftahul Huda, Muhammad Teguh Andriansyah, Hidayat, Paduloh (ADISAM PUBLISHER, 2025)
In the current era of globalization, the agricultural sector has experienced rapid progress in terms of technology, one of which is a sensor system that measures soil water content. This system was created with the aim of helping farmers not to experience difficulties in maintaining soil moisture in order to keep plants from lacking water. This study uses a quantitative and experimental approach. Quantitative is used to measure soil moisture levels systematically, experimentally carried out by designing, assembling, and testing a soil water content measurement system. The designed system consists of several main components, namely Arduino Uno as a control center, a soil moisture sensor to detect water content, a Bluetooth communication module for sending data, and a power source in the form of a 9V battery. The test results show that the developed system design functions very well and meets the stated objectives. The use of Arduino Uno as the main microcontroller provides fast and efficient data processing capabilities, so that the system can respond to changing conditions in a timely manner